177k views
4 votes
Simiplify (3a2+1)−(4+2a2). Write the answer in standard form

User Sectus
by
4.7k points

2 Answers

4 votes

Final answer:

To simplify the expression
(3a^2+1)-(4+2a^2), distribute the negative sign and combine like terms. The simplified expression is
a^2 - 3.

Step-by-step explanation:

To simplify the expression
(3a^2+1)-(4+2a^2), we need to remove the parentheses and combine like terms. First, distribute the negative sign in front of the second set of parentheses:


(3a^2 + 1) - (4 + 2a^2) = 3a^2 + 1 - 4 - 2a^2

Next, combine like terms by adding or subtracting coefficients of the same degree terms:


3a^2 - 2a^2 + 1 - 4 = (3 - 2)a^2 + (1 - 4) = a^2 - 3

Therefore, the simplified expression is
a^2 - 3, written in standard form.

User Achraf JEDAY
by
5.4k points
3 votes

Answer:

-6^4+8x^2-4

Step-by-step explanation:

(3a^2+1)(-2a^2-4)

3a square x -2a square= -6^4

3a square x 1= 3x square -2x^2 x -4=8x^2

3x square + 8x^2= 11x^2

-4 x 1 =-4

User Foolbear
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.